Stitching Snow - Lewis, R. C. (Rachel Christine), 1979- (Hyperion, 2014)
A futuristic retelling of Snow White in which seventeen-year-old Essie, a master at repairing robots and drones on the frozen mining planet Thanda, is pulled into a war by handsome and mysterious Dane after his shuttle crash-lands near her home.